(untitled) (Ticontre. Theory Text Translation, 2020)
The essay delves on the relationship between Ovid and Pavese as emerging in Dialoghi con Leucò. Moving from the most recent theoretical tools outlined by classical reception studies, it focuses on two dialogues: Il fiore and Schiuma d’onda. Therefore, the study outlines their main classical hypotexts (linked to the Metamorphoses as well as to other Ovid’s texts) and it sets Pavese’s rewriting against the backdrop of other Ovidian rewritings of the nineteenth century. In this way, the essay proposes a new evaluation of the Ovidian influence on Pavese’s mythical work, which, as read through the perspective of metamorphosis, can be included in the interest for classical myth typical of the modernist movement.